Mediator-based communication, negotiation and scheduling for decentralised production management - Seilonen, Ilkka (2010)
Recent trends in industry towards autonomous and co-operative production systems and latest developments in data network technologies have created new opportunities for enhancing the co-operation of production networks. In order to take advantage of the emerged opportunities, an approach based on a software system called Mediator has been developed. The Mediator provides order planning support necessary to integrate decisionmaking and scheduling of several actors in decentralised business organisations. The approach will be demonstrated in the context of order planning in multi-site and supplychain production.